2008
DOI: 10.1677/joe-07-0536
|View full text |Cite
|
Sign up to set email alerts
|

Direct effects of prolactin and dopamine on the gonadotroph response to GnRH

Abstract: The intrapituitary mechanisms underlying the inhibitory actions of hyperprolactinaemia on the reproductive axis remain unclear. Previous work on primary pituitary cultures revealed combined suppressive effects of prolactin (PRL) and dopamine on the gonadotrophin response to GnRH. However, whether these effects occur directly at the level of the gonadotroph and are accompanied by changes in gene expression is still unresolved. Here, aT 3 -1 and LbT2 cells were used to investigate the effects of PRL and dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 50 publications
(36 reference statements)
4
27
1
1
Order By: Relevance
“…We observed a clear dose-response curve (data not shown), with maximal stimulation at 10 Ϫ8 M (Fig. 8), consistent with previous reports (49). We then examined the inhibitory effect of mRFRP at concentrations of 10 Ϫ7 to 10 8-CPT-cAMP (a cell-permeable cAMP analog) for 10 min.…”
Section: Inhibitory Effect Of Mrfrp On Lh Releasesupporting
confidence: 88%
“…We observed a clear dose-response curve (data not shown), with maximal stimulation at 10 Ϫ8 M (Fig. 8), consistent with previous reports (49). We then examined the inhibitory effect of mRFRP at concentrations of 10 Ϫ7 to 10 8-CPT-cAMP (a cell-permeable cAMP analog) for 10 min.…”
Section: Inhibitory Effect Of Mrfrp On Lh Releasesupporting
confidence: 88%
“…Prolactin (PRL), the hormone product of lactotroph cells, acts on gonadotrophs cells to modulate the secretion of LH (Cheung 1983, Hodson et al 2010a. Lactotrophs are also estrogen sensitive, and gonadotrophs express PRL receptors (Henderson et al 2008). This evidence further signifies that, in addition to their function in the gonadotroph cells, the genes presented in this study may further modify the LH surge through their actions in lactotroph physiology.…”
Section: Discussionsupporting
confidence: 52%
“…The most probable mechanism of noncycling caused by high levels of serum PRL is inhibition of gonadotropin releasing hormone (GnRH) secretion by a PRL-induced increase in dopamine secretion [6]. A previous paper reported that the LH mRNA response to GnRH was suppressed by PRL [18]. Moreover, PRL inhibits the expression of LH receptors (LH-R) in rats in a dose-dependent manner in granulosa cells treated with FSH [20].…”
Section: Discussionmentioning
confidence: 99%